Accountability of algorithms in data management of data subjects and business users - Davide Mula (Market and Competition Law Review)
This paper intends to investigate the processing and exploitation of data (whether personal and not) through algorithms to understand the profiles of responsibility and the related mechanisms of accountability. In particular, the paper will try to understand how the security of automated and algorithmic decision-making processes can be verified ex post, due to their impact on privacy of both public and private entities.